The effect of puzzle play therapy on the anxiety level of hospitalization of pre-school age children: A literature review - Saputra, Aji; Gurning, Maylar; Mannopposem, Inggerid A (Indonesian Journal of Health Services, 2024)
Background: Hospitalization often generates anxiety among preschool-aged children because unfamiliar environments and medical procedures create emotional stress during treatment. Therapeutic play interventions have been widely implemented to support psychological adaptation during pediatric hospitalization. Objective: This study aimed to examine the effect of puzzle play therapy on the anxiety level of hospitalization among preschool-aged children through a literature review approach. Methods: The study applied a literature review design following the PRISMA guideline from the EQUATOR Network. Secondary data were collected from scientific articles retrieved through Google Scholar using keywords related to puzzle play therapy and hospitalization anxiety in preschool children. The inclusion criteria included full-text research articles published between 2019 and 2024 that investigated therapeutic play interventions among hospitalized preschool-aged children. Ten eligible studies were selected after the screening and eligibility process. Data extraction included study characteristics, research design, sample size, intervention type, anxiety measurement instruments, and main outcomes. The findings were synthesized using descriptive analysis and narrative synthesis to identify patterns in puzzle play therapy effectiveness. Results: The review included ten studies conducted in pediatric hospital settings. Most studies applied quasi-experimental or pretest–posttest designs with sample sizes ranging from 24 to 35 children. The results consistently showed that puzzle play therapy significantly reduced anxiety levels among hospitalized preschool children. Several studies reported statistically significant decreases in anxiety scores with p-values below 0.05. Puzzle play therapy also improved emotional comfort and cooperative behavior during hospitalization. Conclusion: Puzzle play therapy represents an effective non-pharmacological intervention that reduces hospitalization anxiety among preschool-aged children. The intervention provides cognitive distraction, emotional engagement, and structured play experiences that help children adapt to stressful hospital environments.